PERAN GURU DALAM MENINGKATKAN MOTIVASI DAN MINAT BELAJAR SISWA KELAS V SDN TAMBAHMULYO 1 - Wann Nurdiana Sari; Murtono Murtono; Erik Aditia Ismaya (Jurnal Inovasi Penelitian, 2021)
Abstrak The purpose of this study was to analyze the role of theachers in increasing motivation and interest in learning for fifth grade students of SDN Tambahmulyo 1. To analyze the supporting and inhibiting factors for teachers in increasing motivation and interest in learning for fifth grade students of SDN Tambahmulyo 1. This research was conducted because of the low motivation and interest in learning. The research method used is qualitative with descriptive qualitative with descriptive qualitative data analysis. Collecting data in this study were observastion, interviews, field notes, and documentation. The results showed that the role of the teacher in increasing the learning motivation of the fifth grade students of SDN Tambahmulyo 1 is as an informatory, director, motivator, evaluator, and mediator. Meanwhile, the role of the teacher in increasing student interest in learning in grade V SDN Tambahmulyo 1 is by providing learning facilities, organizing learning, using media, and applying creative ideas in learning. The supporting factors for teachers in increasing student motivation and interest in learning are the desires of the students themselves, infrastructure, the surrounding environment, and thei families. Inhibiting factors for teachers in increasing student motivation and interest in learning, namely the desire of students to learn, the environment and the parenting styles of students’ parents